A systematic review of invasive non‐native freshwater bivalves - Prestes, Juliani Giselli; Carneiro, Laís; Miiller, Natali Oliva Roman; Neundorf, Ananda Karla Alves; Pedroso, Clemerson Richard; Braga, Raul Rennó; Sousa, Ronaldo; Vitule, Jean Ricardo Simões (Biological reviews of the Cambridge Philosophical Society, 2024)
ABSTRACT The introduction of invasive species has become an increasing environmental problem in freshwater ecosystems due to the high economic and ecological impacts it has generated. This systematic review covers publications from 2010 to 2020, focusing on non‐native invasive freshwater bivalves, a particularly relevant and widespread introduced taxonomic group in fresh waters. We collected information on the most studied species, the main objectives of the studies, their geographical location, study duration, and type of research. Furthermore, we focused on assessing the levels of ecological evidence presented, the type of interactions of non‐native bivalves with other organisms and the classification of their impacts. A total of 397 publications were retrieved. The studies addressed a total of 17 species of non‐native freshwater bivalves; however, most publications focused on the species Corbicula fluminea and Dreissena polymorpha, which are recognised for their widespread distribution and extensive negative impacts. Many other non‐native invasive bivalve species have been poorly studied. A high geographical bias was also present, with a considerable lack of studies in developing countries. The most frequent studies had shorter temporal periods, smaller spatial extents, and more observational data, were field‐based, and usually evaluated possible ecological impacts at the individual and population levels. There were 94 publications documenting discernible impacts according to the Environmental Impact Classification for Alien Taxa (EICAT). However, 41 of these publications did not provide sufficient data to determine an impact. The most common effects of invasive bivalves on ecosystems were structural alterations, and chemical and physical changes, which are anticipated due to their role as ecosystem engineers. Despite a considerable number of studies in the field and advances in our understanding of some species over the past decade, long‐term data and large‐scale studies are still needed to understand better the impacts, particularly at the community and ecosystem levels and in less‐studied geographic regions. The widespread distribution of several non‐native freshwater bivalves, their ongoing introductions, and high ecological and economic impacts demand continued research. Systematic reviews such as this are essential for identifying knowledge gaps and guiding future research to enable a more complete understanding of the ecological implications of invasive bivalves, and the development of effective management strategies.